Fiscal Correction Analysis of Commercial Financial Statements in Determining Corporate Income Tax Payable at PT Bangun Putra Pesaka - Jefry Youce; Indupurnahayu Indupurnahayu; Hurriyaturohman Hurriyaturohman (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2025)
Commercial financial statements prepared based on Financial Accounting Standards (FAS) often give rise to differences with tax regulations, both in terms of recognition, measurement, and the treatment of expenses and income. These differences cause commercial profit not always to be the same as fiscal profit, thus requiring fiscal reconciliation through positive and negative fiscal corrections. This study aims to analyze fiscal corrections to commercial financial statements in determining corporate income tax payable at PT Bangun Putra Pesaka. The research method used is descriptive with a qualitative approach. The research data consist of secondary data obtained from the company’s commercial financial statements for the year 2019, fiscal reconciliation data, and relevant tax regulations. Data collection techniques were carried out through documentation studies and literature reviews. Data analysis was conducted by identifying accounts that require fiscal correction, classifying fiscal corrections into positive and negative corrections, preparing fiscal reconciliation, and calculating corporate income tax payable. The results of the study indicate that the main fiscal corrections are caused by differences in the treatment of maintenance and repair expenses as well as fixed asset depreciation. These fiscal corrections affect the amount of taxable income and corporate income tax payable. This study concludes that proper fiscal reconciliation is very important to ensure tax compliance and to avoid errors in tax calculations. Keywords: Fiscal Correction; Fiscal Reconciliation; Commercial Financial Statements; Corporate Income Tax.